Pengaruh Kepemimpinan Birokrasi dan Implementasi Electronic Government Terhadap Kualitas Pelayanan Publik Kependudukan dan Pencatatan Sipil di Kota Cilegon - Mas Wigrantoro Roes Setyadi (Sawala : Jurnal Administrasi Negara, 2019)
ABSTRACT One of the supporting factors for the success of the bureaucracy in carrying out its functions as executor of public services is the existence of quality of bureaucratic leadership. As a means of improving the quality of public services organized by the bureaucracy, some developed countries have implemented Electronic Government. This study aims to explore new concepts for the development of bureaucratic leadership theory and electronic government implementation of the quality of public services. The design of the study used a quantitative approach to test the truth of the theory against empirical reality from the influence of bureaucratic leadership variables (X1) and the implementation of Electronic Government (X2) on the quality of public services (Y). The results of this study, Bureaucratic Leadership proved to have a positive effect on Public Service Quality, amounting to 39.6%. The implementation of Electronic Government proved to have a positive effect on the Quality of Public Services, amounting to 33.9%. Bureaucratic leadership and Electronic Government Implementation together have a positive effect on the Quality of The Population and Civil Registration services in the Cilegon Municipality Population and Civil Registration Agency, at 28.6%. In order to preserve this positive influence, Cilegon Municipality Bureaucracy leaders are advised to continue to improve: Employee Motivation, Employee Quality, Effectiveness of Electronic Government-based Service Socialization, Electronic Government-based Organizational Culture, and e-Leadership.Keyword: Bureaucratic Leadership, Electronic Government, Public Services ABSTRAKSalah satu faktor penunjang keberhasilan birokrasi dalam menjalankan fungsinya sebagai pelaksana pelayanan publik adalah adanya kepemimpinan birokrasi yang berkualitas. Sebagai sarana dalam upaya meningkatkan kualitas pelayanan publik yang diselenggarakan oleh birokrasi, beberapa negara maju mengimplementasikan Electronic Government. Penelitian ini bertujuan untuk menggali konsep  baru bagi pengembangan teori Kepemimpinan Birokrasi dan Implementasi Electronic Government terhadap Kualitas Pelayanan Publik. Desain penelitian yang digunakan dengan pendekatan kuantitatif untuk menguji kebenaran teori terhadap kenyataan empirik dari pengaruh variabel kepemimpinan birokrasi (X1) dan implementasi Electronic Government (X2) terhadap kualitas pelayanan publik (Y). Hasil penelitian ini, Kepemimpinan Birokrasi terbukti berpengaruh positif terhadap Kualitas Pelayanan Publik, sebesar 39.6%. Implementasi Electronic Government terbukti berpengaruh positif terhadap Kualitas Pelayanan Publik, sebesar 33.9%. Kepemimpinan Birokrasi dan Implementasi Electronic Government secara bersama berpengaruh positif pada kualitas Pelayanan Publik Kependudukan dan Pencatatan Sipil di Dinas Kependudukan dan Pencatatan Sipil Kota Cilegon sebesar 28,6%. Guna menjaga kelestarian pengaruh positif ini, pimpinan Birokrasi Kota Cilegon disarankan untuk terus meningkatkan: Motivasi Pegawai, Kualitas Pegawai, Efektifitas Sosialisasi Pelayanan berbasis electronic Government, Budaya Organisasi berbasis Electronic Government, dan e-Leadership.Kata Kunci: Kepemimpinan Birokrasi ,E-Government, Pelayanan Publik.